Evaluation of Intraoperative, Local Site Injections of Liposomal Bupivacaine as an Alternative to Standard Local Anesthetics in Patients Undergoing Total Hip Arthroplasty. (August 2020) - Rainville, Edward C.; Asche, Carl; Ren, Jinma; Kim, MinChul; Walker, Lucas; Maurer, B. Ted; Knolhoff, Daniel R.; Shick, Kyle M.
Background: Achieving postsurgical pain control after total hip arthroplasty (THA) is a critical factor for successful recovery because inadequately treated pain may lead to a delay in ambulation and hospital discharge and have an adverse impact on a patient's quality of life.Objective: This study compares the effectiveness of immediate-release local anesthetics for pain control in THA vs liposomal bupivacaine (LB) related to patient outcomes and costs of care.Methods: This is a retrospective cohort study of consecutive patients undergoing THA at 3 hospitals from January 2013 to July 2016. The control group received plain bupivacaine or ropivacaine while the study group received LB. Generalized linear models were used controlling for several patient factors. Primary measures included length of stay (LOS), hospitalization costs, pain relief, opioid use, and mobility. Secondary outcomes were discharge disposition and 30-, 60-, and 90-day readmissions.Results : One hundred and ninety-six patients were identified, with 103 as controls, 70 receiving LB, and 23 excluded. The LB group showed a decrease in LOS of 0.5 days (2.5 ± 2.6 vs 3.0 ± 2.1 days, P = .010), increased mobility on the day of surgery (27.6 ± 49.3 vs 12.5 ± 48.5 feet, P = .001) and the first day after surgery (186.8 ± 133.8 vs 155.2 ± 135.6, P = .039), and decreased hospital costs ($10 670 vs $11 351, P = .022). There were no significant differences in pain scores, opioid use, adverse events, discharge disposition, or readmissions. Study limitations include retrospective analysis, unblinded participants, and generalizability of results.Conclusions : LB provides an effective alternative to standard local anesthetics in patients undergoing THA based on improvements of inpatient parameters, LOS, and cost measures.